Association of MicroRNA-196a-2 Gene Polymorphism with Gastric Cancer Risk in a Chinese Population - Peng, Sheng; Kuang, Zhongshen; Sheng, Chenyi; Zhang, Yan; Xu, Hang; Cheng, Qinghong (Digestive diseases and sciences, 2010)
Background It has been proposed that single nucleotide polymorphisms (SNPs) in microRNAs (miRNAs) could affect the expression of the miRNA and contribute to the susceptibility of human tumors. However, the role of genetic variant (T/C) in miR-196a-2 in gastric cancer susceptibility is still unknown. Objectives To evaluate the association between genetic polymorphism of miR-196a-2 (rs11614913) and risk of gastric cancer, a hospital-based case-control study was conducted in a Chinese population. Methods The miR-196a-2 polymorphism was determined using the method of polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) in 213 gastric cancer patients and 213 age- and sex-matched controls. Results In the present study, we found that a significantly increased risk of gastric cancer in subjects with the variant homozygote CC of miR-196a-2 compared with wild-type homozygote TT and heterozygote CT carriers (adjusted odds ratio (OR) = 1.57, 95% confidence interval (CI) = 1.03-2.39, P = 0.038). Stratified analyses indicated that the variant homozygote CC genotype had a strong association with lymph node metastasis of gastric cancer (adjusted OR = 2.25, 95% CI = 1.21-4.18, P = 0.011). Conclusions These findings suggest that the genetic variant within miR-196a-2 could play an important role in the development and progression of gastric cancer. We expect the findings may be helpful to better understand the mechanism of gastric carcinogenesis.